A case of urgent colonoscopic hemostasis of a cecal hemorrhagic ulceration in a patient receiving heparin for COVID‐19 coagulopathy - Naohisa Yoshida; Ryohei Hirose; Makoto Watanabe; Masaski Yamazaki; Satoru Hashimoto; Shin Matsubara; Yu Kasamatsu; Naohisa Fujita; Rafiz Abdul Rani; Osamu Dohi; Ken Inoue; Yuji Naito; et al. (JGH Open, 2021)
Abstract COVID‐19 rarely causes lower gastrointestinal bleeding even though its RNA has been detected in patient's stool. Urgent colonoscopy in a COVID‐19 patient with massive bloody stool requires various procedural and equipment considerations. Here, we present a case of colonoscopic hemostasis of a cecal hemorrhagic ulceration in a patient on heparin for COVID‐19 coagulopathy. We also share various management methods for the prevention of COVID‐19 contamination. A 71‐year‐old man was diagnosed with COVID‐19 pneumonia and subsequently underwent hemodiafiltration. Heparin was initiated for COVID‐19 coagulopathy. At day 42, the patient experienced 2000 mL of bloody stool. An operator performed urgent colonoscopy with three assistants in a negative‐pressure room with full personal protective equipment. A hemorrhagic ulceration was detected at the cecum, and endoscopic hemostasis was performed. Immunohistochemistry was positive for cytomegalovirus. Postprocedure, the endoscopic systems were thoroughly cleaned, and specific measures for endoscope reprocessing and disinfection were performed to prevent contamination with COVID‐19.